POLYMERS FOR APPLICATION IN INDUSTRIAL FIRE RETARDANT REACTIVE COATINGS - ВАХІТОВ, Р. А.; КАЛАФАТ, К. В.; ТАРАН, Н. А.; БЕССАРАБОВ, В. І.; ВАХІТОВА, Л. М. (Technologies and Engineering, 2024)
Purpose. To investigate the effect of polymer structure on the fire retardant efficiency of intumescent systems based on ammonium polyphosphate/melamine/pentaerythritol for the development of competitive industrial reactive coatings. Methodology. A fire retardant mixture of ammonium polyphosphate/ melamine/pentaerythritol/polymer was chosen as a model intumescent system. Vinyl acetate, acrylic, and styrene-acrylic aqueous dispersions, as well as solutions of their analogs in organic solvents, were used as polymer components. The volumetric intumescent coefficient (K, cm³/g) and mass of char residue (m, %) of the intumescent composition were determined after exposing samples of the intumescent system to temperatures ranging from 200 to 800 °C. Infrared spectroscopy was employed to identify the thermal decomposition products of intumescent systems. Fire retardant efficiency of intumescent coatings was assessed using a mini-furnace under standard fire conditions, according to DSTU B V.1.1-14:2007 and DSTU B V.1.1-13:2007. Findings. The study provides practical recommendations for the development of intumescent coatings with a proven fire resistance limit of R150 by examining the influence of the polymer component nature. It has been demonstrated that the use of different polymers for fire retardant coatings is a method for differentially developing fire protection means focused on a given fire resistance class. It has been demonstrated that to ensure a low fire resistance limit (30 min), it is advisable to use acrylate intumescent coatings, for example, Hydro Pliolite 211 polymer for waterborne paints, or mixtures of Pliolite AC80 and Pliolite AC4 polymers for organosoluble paints. For higher fire resistance values (60 minutes and above), vinyl acetate-type intumescent coatings (vinyl acetate-ethylene, vinyl acetate-ethylene-vinyl versatate) based on aqueous dispersions of polymers such as Vinapas, Mowilith, or similar materials from other manufacturers prove effective. Originality. It is shown that an important factor in improving the fire protection efficiency of intumescent systems is the use of polymers of a specific structure with multistage thermal decomposition. Practical value. Optimal polymer materials applicable for the production of reactive coatings on an industrial scale have been identified.